C Coaching Pengisian BKD Berbasis SISTER Bagi Dosen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Lamongan - Yulie Wahyuningsih; Suyitno Suyitno (Cv. Utility Project Solution, 2023)
The issuance of regulations regarding filling out Lecturer Performance Expense (BKD) reports through the Integrated Resource Information System (SISTER) presents problems regarding the difficulty of operating a system that has interface complexity, lack of knowledge to calculate workload accurately and update information on the results of carrying out lecturer assignments. This activity aims to enable lecturers to be able to manage workloads efficiently, to improve the quality of the implementation of education, research, community service and other supporting activities within the Faculty of Economics and Business, Muhammadiyah University of Lamongan. This activity was carried out in the form of an interactive workshop, to provide lecturers with a comprehensive understanding of filling in workloads through the SISTER system, starting from using the application to the correct filling process. Furthermore, personal assistance was carried out by the facilitating team as well as creating online discussion forums using the WhatsApp platform as a medium of communication and sharing information periodically according to the problems of each lecturer. This activity is able to provide an understanding of the SISTER system which has interface complexity so that it can fill in the BKD smoothly, realize adequate document quality and reflect the implementation of the Tridharma. In addition, participants have the skills to calculate workload according to the activities carried out, can manage a structured performance document storage system and maintain data security properly. This PKM activity also gave rise to collective awareness about the importance of building collaboration and synergy between colleagues.